Cooperative Institutional Research Program (CIRP) (United States): Freshman Survey, 1976 ([Verlag nicht ermittelbar], 2002)
The principal purposes of this national longitudinal study of the higher education system in the United States are to describe the characteristics of new college freshmen and to explore the effects of college on students. For each wave of this survey, each student completes a questionnaire during freshman orientation or registration that asks for information on academic skills and preparation, high school activities and experiences, educational and career plans, majors and careers, student values, and financing college. Other questions elicit demographic information, including sex, age, parental education and occupation, household income, race, religious preference, and state of birth. Specific questions asked of respondents in the 1976 survey included how well the students felt that their high school prepared them in different academic areas, their choice of a particular college, number of children the students expected to have, factors influencing their decision to attend college, and general information about their parents. Respondents were also asked to list their probable career choice, their assessments of achieving certain goals during their college years, and their predictions about what opportunities they might have in the future.